Solving Schrödinger equation by meshless methods - Montegranario, H.; Londoño, M.A.; Giraldo-Gómez, J.D.; Restrepo, R.L.; Mora-Ramos, M.E.; Duque, C.A. (Revista Mexicana de Física E, 2016)
In this paper we apply a numerical meshless scheme for solving one andtwo dimensional time independent Schrödinger equation by means ofcollocation method with Radial Basis Functions interpolants. Inparticular we approximate the solutions using multiquadrics.The method is tested with some of the well-known configurations ofSchrödinger equation and compared with analytical solutions,showing a great accuracy and stability. We also provide some insight on howto use meshless algorithms for obtaining the eigenenergies and wavefunctionsof one- and two-dimensional Schrodinger problems.